MANGROVES OF LATIN AMERICA - Sócola Sánchez, Jacqueline. (2020)
Mangrove ecosystems dominate coastal wetlands in tropical and subtropical regions around the world. Biologically they are among the most important and productive ecosystems, because they provide goods and services to society (Kumar et al., 2014). Among the ecological and economic services, they provide, we can mention raw materials and food. They are important habitats and sources for other marine products (shellfish, crabs, fish, shrimp, many of the commercially important marine species spend part of their early cycle of life in these ecosystems). In addition, it contributes to the protection of coastal areas from erosion, water filtration, medicinal ingredients, tourist attraction, water purification, recreation, education and research (Kumar et al., 2014; Burgess, Li and Qin, 2015; Kuenzer et al., 2011; Blasco, Saenger and Janodet, 1996). Mangroves can filter out pollutants from the sea and sequester carbon dioxide (CO2) released into the atmosphere due to anthropogenic activities (Heumann, 2011; Chen et al., 2013). They are also essential for maintaining beach stability and trapping sediment from river runoff. Mangroves are one of the most vulnerable ecosystems and have decreased dramatically in the last half century (Kuenzer et al., 2011; Vo et al., 2013; World Wildlife Fund, 2017). The main threats to mangroves.are the overexploitation of its natural resources, deforestation, mine activities, pollution and industrial or urban development that extend along coastal forest areas, but especially their conversion to aquaculture (Vo et al., 2013; Hamilton and Lovette, 2015; World Wildlife Fund, 2017). Between 30 and 40 % of the total world mangrove area has been converted to aquaculture in the last 50 years (Hamilton and Lovette, 2015; World Wildlife Fund, 2017). Coastal development, which converts these forests to other land uses, has often ignored the services that mangroves can provide, leading to irreversible environmental degradation (Chen et al., 2013). International programs, such as the Ramsar Convention on Wetlands of the Kyoto Protocol, emphasize the importance of immediate protection measures and conservation activities to prevent further destruction of mangroves (Kuenzer et al., 2011). Despite the conversion rates of mangroves into aquaculture and the fact that mangroves have a much higher carbon level per unit area than other tropical forests, their spatio-temporal evolution is not well known in Ecuador (Hamilton and Lovette, 2015). Current knowledge of the distribution, abundance and conditions of mangroves is essential for the development of management plans and programs for the conservation of these ecosystems. This study is an attempt to answer this concern by analyzing the spatial and temporal dynamics of mangrove forests in the Gulf of Guayaquil estuary, representing an emblematic site of mangrove anthropization in Ecuador.